PERKEMBANGAN TEKNOLOGI DIGITAL DAN DAMPAKNYA TERHADAP KEHIDUPAN MASYARAKAT - Ismi Maesarah; Luthfi Daffa Arfiandi; Salis Ati Diana; Adz Kirani Safitri; Cikha Nur Azizah; M.Gading .J.Z. Nugroho; Muthiah Hafid; Arif Widagdo (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The development of digital technology has brought significant changes to various aspects of society, including education, the economy, social life, and culture. This study aims to analyze the development of digital technology and its impact on society. The method used is a qualitative approach employing a literature review technique, which involves examining various sources such as scientific journals, books, and relevant articles. The findings indicate that digital technology has positive impacts, such as easier access to information, increased efficiency, and the opening of economic opportunities and more innovative learning. However, digital technology also has negative impacts, such as dependency, health issues, a decline in the quality of social interactions, and risks related to data security and the spread of misinformation. Therefore, efforts to improve digital literacy are necessary so that society can utilize technology wisely and responsibly. With proper management, digital technology can provide optimal benefits for human life.